Implementasi Digital Financial Reports Pada Cafe Badan Usaha Milik Desa - Chandra Yudhatama; Firman Husain (Universitas Hasanuddin, 2022)
The role of BUM Desa is very important in the village economy. This means that BUM Desa must provide a profit margin for the village that can be measured, through financial reports. The BUM Desa Financial Report aims to provide information on the position and financial performance of BUM Desa that is useful for users in decision making by the management and the village government in general. Therefore, the author makes the target in this activity is BUM Desa in Panyangkalang Village, Mangarabombang District, Takalar Regency. Based on the interviews conducted, information was obtained that the BUM Desa management had difficulties in preparing financial reports. So, the author makes a financial report format where users only need to make a general journal, then automatically the balances in the Profit and Loss Statement, Changes in Capital Report, and Statement of Financial Position will change according to the journaling done. The difference between this format and the format that is usually used is that it is simpler, easier to use, and still provides reliable data for decision making by BUM Desa managers. This format is also equipped with account explanations and journaling tutorials, to make it easier for BUM Desa managers in compiling their financial reports. The conclusion of this activity is that the report format has been submitted directly to the Head of BUM Desa Panyangkalang on January 18, 2022 and has been used to report BUM Desa finances to the Panyangkalang Village Government.